M269 The Emotional Turmoil Of Ipf. (10th November 2014) - Wibberley, S; Ochiai, Y; Pitt, R; Mathieson, N
Abstract : Background: Our aim was to understand the emotions patients experience in IPF, from initial symptoms to IPF specialist management. Methods: Market research was conducted with an independent agency. Patients with IPF were asked to record a personal account of their experience on a hand-held camera. Face to face interviews with patients were conducted in their home. Carers were also interviewed to add an alternative perspective. Results: The sample included 13 male and 3 female patients with IPF. Patients with lung function impairment of all severities were included, five patients were treated with oxygen therapy and another had received a lung transplant. Many patients had a very active lifestyle before developing IPF, leading to a high degree of frustration with the limitations imposed on their physical ability. A protracted time to diagnosis of a rare lung disease while symptoms progressed often led to distrust with their primary healthcare physician. Lack of expert knowledge about the condition often resulted in variable handling of the situation, with patients often finding themselves involved in a type of 'role-reversal' whereby they informed their primary healthcare physician about their own condition. IPF specialists were perceived as their "guardian angels". Despite being given a terminal diagnosis, patients felt reassured that they were receiving appropriate management for their condition. This stemmed from the perception that specialists treating them had appropriate knowledge and a feeling they were supported by the specialist team. Conclusions: As with other rare diseases, patients appear to gain most reassurance from HCP's with a clear understanding of their condition. This highlights the benefit of expert multidisciplinary teams for IPF.